1980
DOI: 10.1002/em.2860020104
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific induction of sister chromatid exchanges by ethyl carbamate in mice

Abstract: Sister chromatid exchange (SCE) techniques were used to analyze the genetic effects of ethyl carbamate (urethane) in cultured mouse-bone marrow cells, and in several different mouse tissues in vivo. Ethyl carbamate concentrations up to 5.0 mg/ml were ineffective in causing a significant elevation of SCE in vitro. After in vivo drug administration, bone marrow, liver and spermatogonial cells all revealed significant dose-related increases in SCE. Baseline and relative incremental levels of SCE were somatic vs g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 43 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…injections of urethane at 50 to 400 mg/kg (Roberts and Allen, 1980). Dose-related increases in SCEs have been found in bone marrow and liver cells of mice following i.p.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…injections of urethane at 50 to 400 mg/kg (Roberts and Allen, 1980). Dose-related increases in SCEs have been found in bone marrow and liver cells of mice following i.p.…”
Section: )mentioning
confidence: 99%
“…To date, the only direct evidence that urethane causes DNA damage in vivo in germ cells has been provided by Roberts and Allen (1980). These authors showed that urethane caused a dose-dependent increase of SCEs in mouse spermatogonia.…”
Section: ) Germ Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urethane is known to be carcinogenic in animals, producing mammary, lung, and liver tumours in rats and mice [16,17]. It is also genotoxic: a single subcutaneous, intraperitoneal (ip) or intravenous injection of 50 mg/kg bwt or more has induced chromosome damage (aberrations, micronuclei or sister chromatid exchanges) in various tissues, including the bone marrow, lungs, blood lymphocytes, spleen, liver cells and sperm of mice, rats, and hamsters [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Russell et al [ 19871, using the mouse specific locus mutation assay, found no significant induction of mu-tations by EC in spermatogonial and postspermatogonial stages of male mice. To our knowledge, the only consistent evidence that EC may be genotoxic to mouse spermatogonia has come from Roberts and Allen [1980]. These authors reported that EC induced a low but statistically significant increase in sister chromatid exchanges in mouse spermatogonia.…”
Section: Introductionmentioning
confidence: 96%